1993
DOI: 10.1161/01.cir.87.5.1524
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin versus coumadin in the prevention of reocclusion and recurrent ischemia after successful thrombolysis: a prospective placebo-controlled angiographic study. Results of the APRICOT Study.

Abstract: At 3 months after successful thrombolysis, reocclusion occurred in about 30% of patients, regardless of the use of antithrombotics. Compared with placebo, aspirin significantly reduces reinfarction rate and revascularization rate, improves event-free survival, and better preserves left ventricular function. The efficacy of Coumadin on these end points appears less than that of aspirin. The still-high reocclusion rate emphasizes the need for better antithrombotic therapy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(82 citation statements)
references
References 19 publications
1
76
1
4
Order By: Relevance
“…Three months after successful thrombolytic therapy, the reocclusion rate may be as high as 30%. 10,11 High reocclusion rates have also been documented 6 months after PTCA of an IRA. 12,13 Few studies have been designed to analyze the impact of late reocclusion of the IRA on long-term prognosis.…”
mentioning
confidence: 99%
“…Three months after successful thrombolytic therapy, the reocclusion rate may be as high as 30%. 10,11 High reocclusion rates have also been documented 6 months after PTCA of an IRA. 12,13 Few studies have been designed to analyze the impact of late reocclusion of the IRA on long-term prognosis.…”
mentioning
confidence: 99%
“…The study protocols of the APRICOT-1 (1987)(1988)(1989)(1990)(1991) and APRICOT-2 (1995APRICOT-2 ( -2000 trials have been reported in detail previously [17,18].…”
Section: Protocolmentioning
confidence: 99%
“…In APRICOT-1 reocclusion was defined as ECSG grade 4 (91-99% diameter stenosis, no complete filling within 3 cycles) or grade 5 stenosis (total occlusion with or without collateral filling) [17]. In APRICOT-2 the definition of reocclusion was TIMI flow grade 2 or less [18].…”
Section: Cardiac Catheterizationmentioning
confidence: 99%
See 2 more Smart Citations